ETH‐LEACH: An energy enhanced threshold routing protocol for WSNs. (27th May 2021) - Chithaluru, Prem Kumar; Khan, Mohammad S; Kumar, Manoj; Stephan, Thompson
Summary: Many wireless sensor‐based applications use LEACH as a preferred routing protocol owing to its unique features such as optimal sleeping time, minimum packet collisions, dynamic channel selection, and least power consumption. The traditional LEACH protocol wastes the transmission opportunities as it processes data only in an event occurring, leading to wastage of resources. To resolve this issue, this paper proposes a more robust Energy Enhanced Threshold Routing Protocol (ETH‐LEACH) for WSNs. The working of ETH‐LEACH is conceptualized in two parts. In the first part, TDMA is implemented to estimate the opportunistic paths to remove network overhead. Furthermore, in the second part, a threshold value is calculated for choosing the forwarder nodes. The proposed technique minimizes the energy usage of the sensor nodes and consequently enhances the network's lifetime by extending the duration of node death. The ETH‐LEACH protocol is contrasted with the different variants of LEACH to verify its effectiveness. The experimental results show that the proposed ETH‐LEACH protocol outperforms the traditional routing protocols. In this paper, the ETH‐LEACH protocol performs nearly 54.6% efficient than LEACH, 47.6% efficient than Q‐LEACH, 41.3% efficient than NR‐LEACH, 33.6% efficient than LEACH‐GA, and 29.7% efficient than LEACH‐POS in reducing the usage of energy in the overall simulation. Abstract : This paper uses threshold energy for identifying the best FNs for sending packets to the CH and CH to BS. ETH‐LEACH protocol uses the adaptive ranking and threshold approach to improve the network lifetime metrics such as FND, HND, and LND, and at the same time maximizing the number of packets sent to the BS. ETH‐LEACH routing protocol recognizes the optimal number of FNs to be selected for forwarding the data packets to the BS using the threshold technique. ​